2012
DOI: 10.4103/0971-9784.97975
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weight loss on the outcome after coronary artery bypass grafting in obese patients

Abstract: The role of body mass index (BMI) in the setting of coronary artery bypass graft (CABG) surgery has been a focus of past studies. However, the effects of postoperative weight loss in patients after CABG is yet to be known. We performed a retrospective study of 899 patients who underwent CABG at our institution. Perioperative patient information was collected from an onsite electronic record system. Patients were grouped into four BMI categories: normal controls, overweight, obese and morbidly obese. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Retrospective, observational studies assessing the association between weight loss and clinical outcomes after CABG have shown paradoxical results, with worse outcomes among patients losing weight after CABG. 403 However, these studies could not differentiate between purposeful and unintentional weight loss. Unintentional weight loss could reflect comorbidities such as heart failure, cancer, and lung diseases or may reflect the severity of other conditions associated with decreased survival.…”
Section: Obesity and Metabolic Syndromementioning
confidence: 97%
“…Retrospective, observational studies assessing the association between weight loss and clinical outcomes after CABG have shown paradoxical results, with worse outcomes among patients losing weight after CABG. 403 However, these studies could not differentiate between purposeful and unintentional weight loss. Unintentional weight loss could reflect comorbidities such as heart failure, cancer, and lung diseases or may reflect the severity of other conditions associated with decreased survival.…”
Section: Obesity and Metabolic Syndromementioning
confidence: 97%
“…Several observational studies have shown worse outcomes with weight loss in broad populations ( Karahalios et al, 2014 , Pack et al, 2014 , Myers et al, 2011 , Østergaard et al, 2010 ) and also in specific sub-groups, including individuals with diabetes, ( Lee et al, 2020 ) patients with ischemic stroke ( Wohlfahrt et al, 2015 ) or coronary heart disease, ( Moholdt et al, 2018 ) and those who have undergone coronary artery bypass graft surgery. ( Kocz et al, 2012 ) However, most of these studies could not distinguish between unintentional and intentional weight loss. While unintentional weight loss may be due to underlying cachexic conditions that lead to increased risk of poor outcomes ( De Stefani et al, 2018 ), intentional weight loss would be expected to improve outcomes given associated improvements in glucose, blood pressure, and lipids.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that preoperative unintentional weight loss results in adverse effects on postoperative outcomes [ 32 ]. Moreover, decreased body weight is also observed after cardiac surgery and may intensify problems associated with nutritional status and outcomes, even in those with a high BMI [ 33 ].…”
Section: Discussionmentioning
confidence: 99%